Patient-reported urinary incontinence after radiotherapy for prostate cancer: Quantifying the dose–effect. Issue 1 (October 2017) - Cozzarini, Cesare; Rancati, Tiziana; Palorini, Federica; Avuzzi, Barbara; Garibaldi, Elisabetta; Balestrini, Damiano; Cante, Domenico; Munoz, Fernando; Franco, Pierfrancesco; Girelli, Giuseppe; Sini, Carla; Vavassori, Vittorio; et al.
Abstract: Background and purpose: Urinary incontinence following radiotherapy (RT) for prostate cancer (PCa) has a relevant impact on patient's quality of life. The aim of the study was to assess the unknown dose–effect relationship for late patient-reported urinary incontinence (LPRUI). Methods and materials: Patients were enrolled within the multi-centric study DUE01. Clinical and dosimetry data including the prescribed 2 Gy equivalent dose (EQD2) were prospectively collected. LPRUI was evaluated through the ICIQ-SF questionnaire filled in by the patients at RT start/end and therefore every 6 months. Patients were treated with conventional (74–80 Gy, 1.8–2 Gy/fr) or moderately hypo-fractionated RT (65–75.2 Gy, 2.2–2.7 Gy/fr) in 5 fractions/week with intensity-modulated radiotherapy. Six different end-points of 3-year LPRUI, including or not patient's perception (respectively, subjective and objective end-points), were considered. Multivariable logistic models were developed for each end-point. Results: Data of 298 patients were analyzed. The incidence of the most severe end-point (ICIQ-SF > 12) was 5.1%. EQD2 calculated with alpha–beta = 0.8 Gy showed the best performance in fitting data: the risk of LPRUI markedly increased for EQD2 > 80 Gy. Previous abdominal/pelvic surgery and previous TURP were the clinical factors more significantly predictive of LPRUI. Models showed excellent performances in terms of goodness-of-fit and calibration, confirmed by bootstrap-based internal validation. When included in the analyses, baseline symptoms were a major predictor for 5 out of six end-points. Conclusions: LPRUI after RT for PCa dramatically depends on EQD2 and few clinical factors. Results are consistent with a larger than expected impact of moderate hypo-fractionation on the risk of LPRUI. As expected, baseline symptoms, as captured by ICIQ-SF, are associated to an increased risk of LPRUI.